Healthcare providers' challenges during the coronavirus disease (COVID‐19) pandemic: A qualitative approach. (17th March 2021) - Ness, Michelle M.; Saylor, Jennifer; Di Fusco, Leigh Ann; Evans, Kristen
Abstract: The uncertain trajectory of COVID‐19 has led to significant psychosocial impacts on nurses and other healthcare providers. Given the critical role of these providers in pandemic response, this study sought to gain a better understanding of the challenges faced by healthcare providers caring for adult patients during the COVID‐19 pandemic. A descriptive, qualitative study was conducted via semi‐structured interviews. A purposeful sample of healthcare providers (n = 23) caring for patients during the COVID‐19 pandemic was recruited to participate in interviews via snowball sampling and an information systems‐supported recruiting process (e‐recruiting). Thematic analysis revealed four themes: (1) Managing isolation, fear, and increased anxiety; (2) adapting to changes in healthcare practice and policy; (3) addressing emotional and physical needs of patients and their families; and (4) navigating evolving workplace safety. New evidence was introduced about nurses practicing outside their usual role. Nurses and other healthcare providers consistently reported increased anxiety during the pandemic. Hospital administrations can proactively support healthcare providers during this and future pandemics by ensuring access to mental health programs, standardizing communication, and developing plans that address equipment and supply availability.